The Mobile Politics of Emotions and Social Movement in Oaxaca, Mexico. Issue 5 (2nd June 2015) - Arenas, Iván
Abstract In light of recent debates between affect and emotions in geography, this article focuses on how the emotional landscape of spatial struggles in Oaxaca articulated people together, thereby generating solidarities and a collective sociality offering the potentiality of interconnection that geographers of affect emphasize. Through an analysis of a women's march, I demonstrate how social movements move people, mobilizing them both physically and emotionally, with effects that go beyond a movement's political demands. Engaging with how emotions do movement‐building work means going beyond a focus on the relational construction of emotions and arguing instead for their collective agency, including their power to transform participants into activists. Highlighting the centrality of spatial struggles and emotions to the shifting, mobile politics of social movements brings into sharp relief the importance of a situated, historical analysis for theorists romanticizing the emancipatory possibilities of a revolutionary transnational articulation between social movements.